Keragaman Varietas Mangga (Mangifera indica L.) Di Kotamadya Semarang Jawa Tengah - Utami, Sri; Baskoro, Karyadi; Perwati, Lilih Khotim; Murningsih, M (Bioma : Berkala Ilmiah Biologi, 2019)
Mango is a fruit that is very popular with the community, especially in Semarang. The taste is sweet, refreshing and has a high vitamine content is the reason this fruit has become one of the superior fruit. In the Semarang area there are quite a lot of mango trees with various varieties. These various mango varieties are potential genetic resources that need to be preserved. This study aims to explore the various mango tree varieats that grow in the municipal area of Semarang. Research techniques by exploring in 3 districts are Banyumanik, Tembalang Â and Gunung Pati. The results showed 14 varieties of mango and the most widely grown varieties by the people in the municipality of Semarang are arum manis and manalagi mango. Some of them are local mangoes, mango cultivation and imported mangoes. Local varieties of mango are only found in very small quantities and have begun to scarce, so it is feared that the supply of mango germplasm is increasingly depleting. Germplasm of local mango plants is important to be preserved as a wealth of genetic resources in the Municipality of Semarang